The effect of personalized orthopedic insoles on plantar pressure during running in subtle cavus foot - Ma, Mujia; Song, Qingquan; Liu, Hui (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: This study aims to investigate the patterns of plantar pressure distribution during running for patients with subtle cavus foot (SCF) and determine the impact of personalized orthopedic insoles with forefoot wedge on plantar pressure distribution in patients with SCF. Methods: Sixteen undergraduate participants (8 with SCF and 8 with normal arches) were recruited based on arch height index measurements. Two full-length insoles were personalized for each SCF based on plantar pressures during running, an arch support insole (ASI) and an arch support with forefoot wedge insole (AFI). Foot pressure data collected during different insole conditions in running, analyzing ten regions of footprints for peak pressure and pressure-time integral. Results: Higher peak pressures were observed in patients with SCF at the medial forefoot (p = 0.021), medial heel (p = 0.013), and lateral heel (p = 0.025), with a higher pressure-time integral also noted at the medial forefoot (p = 0.025), medial heel (p = 0.015), and lateral heel (p = 0.047) when compared to normal arches. Compared with without-insole, both the AFI and the ASI reduced peak pressure at the medial (AFI p = 0.011; ASI p = 0.024) and lateral heel (AFI p = 0.028; ASI p = 0.032). The AFI reduced peak pressure at the medial heel (p = 0.013) compared with the ASI. Both the AFI and the ASI reduced pressure-time integral at the medial forefoot (AFI p = 0.003; ASI p = 0.026), central forefoot (AFI p = 0.005; ASI p = 0.011), medial heel (AFI p = 0.017; ASI p = 0.005), and lateral heel (AFI p = 0.017; ASI p = 0.019). Additionally, the ASI reduced pressure-time integral at the big toe (p = 0.015) compared with the without-insole. Conclusions: These findings demonstrate that during running in patients with SCF, plantar pressures are concentrated in the forefoot and heel compared to the normal arch. The personalized orthotic insoles can be used to effectively redistribute plantar pressure in patients with SCF running. Incorporating a forefoot wedge to specifically address the biomechanical abnormalities associated with SCF may enhance the effectiveness of orthopedic insoles.